Al-Akhá¹Äâ€™ An-Naá¸¥wiyyah Laday Aá¹-á¹¬ulab Al-Mubtadi-in fÄ« Al-JÄmiâ€™ah Al-IslÄmiyyah Al- â€˜Ä€lamiyyah Malaysia - Niamin, Agus; Abu Bakar, Radhwa Binti (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
Abstract Syntactic (Naá¸¥w) errors are the subjects of linguistsâ€™ debate that has long lasted without a fairly winning solution.Â However, that solution should be still attempted particularly pertaining to linguistic, logical and syntactic corrections. It is this issue that the present study will deal with mainly in connection with some syntactic errors to which most writing errors have happened. The research will employ selected papers written by students of the International Islamic University Malaysia (IIUM) as the subject of analysis. The studyâ€™s result eventually reveals that syntactic aspect is one of the most frequently happened mistake among Malaysian universities particularly those who are the non-Arabic speaking beginners. Keywords: Grammatical Errors, Junior Students, Error Analysis, Arabic Grammar, Syntactic. Â Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¨ØªØ¯Ø¦ÙŠÙ† ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ù…Ø§Ù„ÙŠØ²ÙŠØ§ Ø±Ø¶ÙˆÙ‰ Ø£Ø¨Ùˆ Ø¨ÙƒØ±ØŒ Ø£ØºÙˆØ³Ù†ÙŠ Ø£Ù…ÙŠÙ† Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù…Ø§Ù„Ø²ÙŠØ§ radhwa@iium.edu.my, agusniamin@gmail.com Ù…Ù„Ø®Øµ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ© Ù‚Ø¶ÙŠØ© ÙƒØ¨ÙŠØ±Ø© Ø§Ù„Ø¥Ø´ÙƒØ§Ù„ÙŠØ© ÙˆØ·ÙˆÙŠÙ„Ø© Ø§Ù„Ù†Ù‚Ø§Ø´ Ø¨ÙŠÙ† Ø§Ù„Ù…ØªØ®ØµØµÙŠÙ† Ø¯ÙˆÙ† Ø£Ù† ØªØµÙ„ Ø¥Ù„Ù‰ ØÙ„ÙˆÙ„Ù‡Ø§ ÙØ¹Ù‘Ø§Ù„Ø©. ÙˆÙ…Ù‡Ù…Ø§ ÙŠÙƒÙ† Ø§Ù„Ø£Ù…Ø±ØŒ ÙØ§Ù„ØªØµØÙŠØ Ø§Ù„Ù„ØºÙˆÙŠ ÙˆØ§Ù„Ø¥ØµÙ„Ø§Ø Ø§Ù„Ù…Ù†Ø·Ù‚ÙŠ Ù…Ù‡Ù…Ø§Ù† Ù„Ø§ Ù†ÙØ± Ù…Ù†Ù‡Ù…Ø§. ÙˆØ¥Ù„ÙŠÙ‡Ù…Ø§ Ù†ØØªØ§Ø¬ Ø¥Ù„Ù‰ ØªØÙ„ÙŠÙ„ ØªÙ„Ùƒ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ©ØŒ Ù„Ø°Ù„Ùƒ Ø¬Ø§Ø¡ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ø¯ÙØ§ Ø¥Ù„Ù‰ Ø§Ù„ØªØ±ÙƒÙŠØ² Ø¹Ù„Ù‰ Ø§Ù„Ø£Ø¨ÙˆØ§Ø¨ Ø§Ù„Ù†ØÙˆÙŠØ© Ø§Ù„ØªÙŠ ÙƒØ«Ø±Øª ÙÙŠÙ‡Ø§ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ØŒ ÙˆØ°Ù„Ùƒ Ø¨ØªØ·Ø¨ÙŠÙ‚Ù‡Ø§ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ù‚Ø§Ù„Ø§Øª Ø§Ù„Ù…Ø®ØªØ§Ø±Ø© Ù…Ù† Ø·Ù„Ø¨Ø© Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ù…Ø§Ù„ÙŠØ²ÙŠØ§. ÙÙ…Ù† Ø®Ù„Ø§Ù„ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ«ØŒ Ø£Ø¯Ø±Ùƒ Ø§Ù„Ø¨Ø§ØØ« Ø£Ù† Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ© ÙˆÙ‚Ø¹Øª Ø¨ÙƒØ«Ø±Ø© Ø¹Ù„Ù‰ ÙƒØªØ§Ø¨Ø§Øª ÙˆÙ…Ù‚Ø§Ù„Ø§Øª Ù„Ù„Ø·Ù„Ø¨Ø© Ø§Ù„Ù…Ø¨ØªØ¯Ø¦ÙŠÙ†Â Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø¨Ù…Ø§Ù„ÙŠØ²ÙŠØ§. ÙƒÙ„Ù…Ø§Øª Ù…ÙØªØ§ØÙŠØ©: Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ©ØŒ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¨ØªØ¯Ø¦ÙŠÙ†ØŒ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ØŒ Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ Ø§Ù„Ù†ØÙˆ Ø§Ù„Ø¹Ø±Ø¨ÙŠ